Makna Karikatur dan Kalimat Satire dalam Kolom “Si Doengil” pada Harian Kalteng Pos - Shiddiqie, Thoyyib Ash; Syah, Hakim; Setiawan, Heri (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This study aims to determine the meaning of visual and verbal signs in the "Si Doengil" column of Kalteng Pos daily newspaper. This research uses Roland Barthes' semiotic analysis to determine the meaning of visual elements in caricatures and satirical sentences in the "Si Doengil" column. The sampling technique used was purposive sampling, where the researcher selected the "Si Doengil" column published in editions 5, 6, 7, 19, 28, 29, and 30 September 2023 to be analysed more deeply. The results showed that the column "Si Doengil" from its naming comes from the Dayak language "Dungil" which means wayward or usil, usil here reflects people who like to be outspoken in commenting and giving criticism. The icon of a child in the caricature "Si Doengil" depicts innocence and broad curiosity in addressing or commenting on hot issues that are happening. From the depiction of expressions in the caricature of "Si Doengil", namely the upturned face, upturned hands, and gaping mouth as if questioning and criticising the issues that are being reported. The "Si Doengil" column was published by Kalteng Pos daily to provide an expression of sentiment, satire, or criticism related to the main news on the first page.